The Era of E-Commerce And Consumer Law: A Review of Protection Implementation in Indonesia - Risma Nur Aqidah (Generate Digital Publishing, 2025)
Objective: The purpose of this study is to explore the challenges and limitations of consumer protection in the Indonesian e-commerce sector, especially related to cross-border transactions. This study also aims to evaluate the effectiveness of existing regulations and propose solutions to strengthen the legal framework to improve consumer protection in online transactions. Research Design & Methods: This study uses a qualitative approach with normative legal methods, collecting data through literature reviews, regulatory analysis, case studies, and interviews with legal experts and e-commerce stakeholders. This study also compares international practices to identify deficiencies in existing consumer protection regulations. Findings: This study concludes that consumer protection laws in Indonesia are not yet effective in handling cross-border e-commerce transactions, with the main problems being weak law enforcement, difficulties in unifying international transactions, and low consumer awareness. In addition, there are challenges in adapting Indonesian laws to technological advances and encouraging international online trade. Implications & Recommendations: This study suggests steps to strengthen consumer protection in e-commerce in Indonesia, such as updating laws, strengthening monitoring, and launching public education campaigns. In addition, it is important to tighten law enforcement and build international cooperation in harmonizing consumer protection laws. Contribution & Value Added: This research will provide insights into the legal challenges in Indonesia's e-commerce market and propose solutions to enhance consumer protection, create a more secure, transparent and reliable ecosystem, and offer a roadmap for other countries in regulating cross-border e-commerce transactions.